APLIKASI PENGGUNAAN BERBAGAI MACAM MIKROALGA POWDER UNTUK PAKAN JUVENIL IKAN BANDENG (Chanos – chanos fork) - Wiwie Soemarjati; Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2013)
This study aims to determine the effectiveness of the use of natural feed powder in increasing the production of juvenile fish. This research are conducted for two months ie from January to March 2013 in Hall Aquaculture brackish (BPAP) Situbondo, using four treatments with two replications: the use of artificial feed / feed larvae (control), Spirullina sp powder, Skeletonema sp powder , Chaetoceros sp powder. Maintenance is carried out for 60 days, with the frequency of feeding 4 times, namely at 6:00, 10:00, 14:00 and 18:00 pm as many as 10% of total body weight. Temperature measurement is carried out every day and other water quality measurement once every week. Parameter research / sampling carried out at D1, D20, D40 and D60 / end maintenance. Data the length and weight of the highest in the treatment of juvenile milkfish larvae feed followed treatment Spirulina sp, Skeletonema sp and Chaetoceros sp. Data highest growth rate in the treatment of feeding the larvae of 0.0093 grams / day, Spirullina sp 0.0075 grams / day, Chaetoceros sp 0.0074 grams / day and Skeletonema sp 0,0063 grams / day. Survival Rate Highest in treatment larvae feed at 99.2% followed treatment Spirullina sp, Chaetoceros and Skeletonema sp sp.. From these results it can be concluded that the microalgae Spirullina sp provide the best data than the use of other microalgae, microalgae use of powder can be used as alternative to feeding on juvenile milkfish